2023
DOI: 10.3390/ani13030432
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant Bacteria Dissemination in the Wildlife, Livestock, and Water of Maiella National Park, Italy

Abstract: Antimicrobial resistance (AMR) is a global health concern that has been linked to humans, animals, and the environment. The One Health approach highlights the connection between humans, animals, and the environment and suggests that a multidisciplinary approached be used in studies investigating AMR. The present study was carried out to identify and characterize the antimicrobial resistance profiles of bacteria isolated from wildlife and livestock feces as well as from surface water samples in Maiella National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Escherichia coli and enterococci isolated in this study show resistance to a wider range of antibiotics compared to the study carried out in the same protected area on domestic and wild ruminants [ 20 , 21 , 22 ]. Furthermore, the MDR E. coli isolates show resistance to critically important antibiotics (enrofloxacin, marbofloxacin, and pradofloxacin).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Escherichia coli and enterococci isolated in this study show resistance to a wider range of antibiotics compared to the study carried out in the same protected area on domestic and wild ruminants [ 20 , 21 , 22 ]. Furthermore, the MDR E. coli isolates show resistance to critically important antibiotics (enrofloxacin, marbofloxacin, and pradofloxacin).…”
Section: Discussionmentioning
confidence: 58%
“…Antibiotic resistance is a growing concern in both human and animal health, and recent studies have suggested that wildlife may serve as sentinels of antibiotic resistance pollution in the environment [ 18 , 19 , 20 , 21 , 22 ]. Furthermore, the issue of antibiotic resistance in wildlife has important implications for conservation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…In healthcare settings, it can be transmitted to humans through contaminated equipment, surfaces, or water sources. It is frequently reported in people with weakened immune systems [ 38 ] and can cause infections of the respiratory tract, urinary tract, bloodstream, and skin. According to Zhang et al [ 39 ], metallo-β-lactamase (MBL)-producing Pseudomonas isolates were found not only in the livestock (presence of Verona Integron-encoded (VIM)-positive Pseudomonas species in chickens), but also in their surrounding environment.…”
Section: Priority Pathogens In Food-producing Animalsmentioning
confidence: 99%
“…This bacterial species is commonly found in the intestinal tracts of animals, particularly poultry and pigs [ 47 , 48 ], and can be transmitted to humans through the consumption of contaminated food or water [ 49 ]. Recently, it has been recognized as the primary culprit for bacterial foodborne illnesses in the U.S. [ 38 ]. C. jejuni causes gastrointestinal illness in humans, characterized by symptoms such as fever, diarrhea, and abdominal cramps.…”
Section: Priority Pathogens In Food-producing Animalsmentioning
confidence: 99%
“…Hence, livestock play a crucial role as a primary source of AMR transmission to wildlife, particularly in the interface regions where livestock and wildlife coexist [36]. The occurrence of ARB in free-living wild life is well documented [37] [38], this phenomenon is particularly observed in areas where domestic animals and wildlife come into contact with each other [39]. Further action necessitates the monitoring and investigation of AMR within the ICLF system.…”
Section: Impact Of Antibiotic Resistance In Iclf Systemmentioning
confidence: 99%